The effect of concurrent visual feedback on controlling swimming speed - Szczepan, S.; Zaton, K.; Klarowicz, A. (Polish Journal of Sport and Tourism, 2016)
Introduction. Developing the ability to control the speed of swimming is an important part of swimming training. Maintaining a defined constant speed makes it possible for the athlete to swim economically at a low physiological cost. The aim of this study was to determine the effect of concurrent visual feedback transmitted by the Leader device on the control of swimming speed in a single exercise test. Material and methods. The study involved a group of expert swimmers (n = 20). Prior to the experiment, the race time for the 100 m distance was determined for each of the participants. In the experiment, the participants swam the distance of 100 m without feedback and with visual feedback. In both variants, the task of the participants was to swim the test distance in a time as close as possible to the time designated prior to the experiment. In the first version of the experiment (without feedback), the participants swam the test distance without receiving real-time feedback on their swimming speed. In the second version (with visual feedback), the participants followed a beam of light moving across the bottom of the swimming pool, generated by the Leader device. Results. During swimming with visual feedback, the 100 m race time was significantly closer to the time designated. The difference between the pre-determined time and the time obtained was significantly statistically lower during swimming with visual feedback (p = 0.00002). Conclusions. Concurrently transmitting visual feedback to athletes improves their control of swimming speed. The Leader device has proven useful in controlling swimming speed.